Mechanical and biological characterization of a composite annulus fibrosus repair strategy in an endplate delamination model. Issue 4 (16th July 2020) - Alexeev, Dmitriy; Cui, Shangbin; Grad, Sibylle; Li, Zhen; Ferguson, Stephen J.
Abstract: This study compares the mechanical response of the commonly used annulus fibrosus (AF) puncture injury model of the intervertebral disc (IVD) and a newly proposed AF failure at the endplate junction (delamination) on ex vivo bovine IVDs. Biocompatibility and mechanics of a newly developed repair strategy comprising of electrospun polycaprolactone (PCL) scaffold and fibrin‐genipin (FibGen) adhesive was tested on the delamination model. The study found no significant difference in the mechanical response to compressive loading between the two models. Primary goals of the repair strategy to create a tight seal on the damage area and restore mechanical properties, while showing minimal cytotoxicity, were broadly achieved. Postrepair, the IVDs showed a significant restoration of mechanical properties compared to the injured samples for the delamination model. The FibGen glue showed a limited toxicity in the AF and produced a resilient and mechanically stable seal on the damaged area. Abstract : The present study investigates the mechanical response of the commonly used annulus fibrosus puncture injury model of the intervertebral disc and a newly proposed avulsion of the endplate junction (delamination) on ex vivo bovine intervertebral discs. Subsequently, biocompatibility and mechanics of a newly developed repair strategy comprising of electrospun polycaprolactone scaffold and fibrin‐genipin (FibGen) adhesive was tested on the delamination model.